Pelatihan Penulisan Artikel Ilmiah dan Manajemen Referensi bagi Dosen Institut Ilmu Kesehatan Pelamonia - Poewanto, Bobby; Aswi, Aswi; Fahmuddin, Muhammad; Sukarna, Sukarna (LPPM Universitas Bumigora, 2023)
In Indonesia, one of the benchmarks for lecturer performance can be noticed from their publications. Therefore, it is important for lecturers to continue improving their knowledge and skills in writing a scientific article such as reference management skills. Prior to the service activities, an analysis of problems related to writing a scientific article was carried out. The service activity began with a pre-test to measure the extent of the participants' understanding in writing a scientific article and reference management. Furthermore, two trainings namely scientific article writing training and reference management training were presented by the speakers. After the training, a discussion session was held between the participants and team. The activity ends with a post-test to measure the extent to which the participants' knowledge and skills have increased in scientific article writing and reference management. Reflection on the implementation of this program is carried out by team leader and team to review all the benefits and weakness of this program and its implementation. Partners in this service are Lecturers of Institut Ilmu Kesehatan Pelamonia with 46 participants. The results achieved in this service are: before the presentation of the material, 75% of the participants still lacked in understanding regarding the writing a scientific article in Reputable International Journals. After the presentation of the material, 93.5% of the participants had understood the writing a scientific article in Reputable International Journals.